The Branched-Chain Amino Acid Aminotransferase Encoded by ilvE Is Involved in Acid Tolerance in Streptococcus mutans - Santiago, Brendaliz (American Society for Microbiology, 2012)
The ability of Streptococcus mutans to produce and tolerate organic acids from carbohydrate metabolism represents a major virulence factor responsible for the formation of carious lesions. Pyruvate is a key metabolic intermediate that, when rerouted to other metabolic pathways such as amino acid biosynthesis, results in the alleviation of acid stress by reducing acid end products and aiding in maintenance of intracellular pH. Amino acid biosynthetic genes such as ilvC and ilvE were identified as being upregulated in a proteome analysis of Streptococcus mutans under acid stress conditions (A. C. Len, D. W. Harty, and N. A. Jacques, Microbiology 150:1353–1366, 2004). In Lactococcus lactis and Staphylococcus carnosus, the ilvE gene product is involved with biosynthesis and degradation of branched-chain amino acids, as well as in the production of branched-chain fatty acids (B. Ganesan and B. C. Weimer, Appl. Environ. Microbiol. 70:638–641, 2004; S. M. Madsen et al., Appl. Environ. Microbiol. 68:4007–4014, 2002; and M. Yvon, S. Thirouin, L. Rijnen, D. Fromentier, and J. C. Gripon, Appl. Environ. Microbiol. 63:414–419, 1997). Here we constructed and characterized an ilvE deletion mutant of S. mutans UA159. Growth experiments revealed that the ilvE mutant strain has a lag in growth when nutritionally limited for branched-chain amino acids. We further demonstrated that the loss of ilvE causes a decrease in acid tolerance. The ilvE strain exhibits a defect in F(1)-F(o) ATPase activity and has reduced catabolic activity for isoleucine and valine. Results from transcriptional studies showed that the ilvE promoter is upregulated during growth at low pH. Collectively, the results of this investigation show that amino acid metabolism is a component of the acid-adaptive repertoire of S. mutans.